Upaya Mengurangi Konsumsi Minuman Beralkohol di Kalangan Muda Lewat Kegiatan GEBRAK (Generasi Bebas Dari Alkohol): Efforts to reduce alcohol consumption among young people through GEBRAK - Yoan, Margaretha Wulan Puspita; Marpaung, Yosi Marin (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Alcohol consumption among young people has become a common practice. Based on interviews, the majority of youth in Association X in Jakarta frequently consume alcoholic beverages. A community service activity titled "A Generation Free from Alcohol" was aimed at increasing knowledge and intentions to reduce alcohol consumption among the youth group in Association X. The methods used included counseling, focused group discussions, and the creation of a shared commitment, which involved 11 key individuals from Association X. The activity began with a pretest to assess knowledge and commitment, followed by the presentation of material on the dangers of alcohol, its effects, and sharing experiences related to overcoming alcohol addiction. This was followed by focused group discussions, presentations of discussion results, a posttest using the same questionnaire, and a joint commitment declaration. The results showed the greatest increase in knowledge regarding ways to overcome alcohol addiction (78.6%), the causes of alcohol addiction (50%), and the negative impact of alcohol on mental health (41.3%). This activity successfully provided cognitive benefits to participants regarding the dangers of alcohol and its effects on the body. However, the activity has not yet optimally reduced the intention to consume alcohol or encourage peers to drink alcoholic beverages. The implication is that similar activities in the future should not only focus on knowledge transfer but also develop strategies that address the antecedents and determinants of young people's intentions to consume alcohol.